Postrzeganie osób z niepełnosprawnością in- telektualną przez studentów kierunków politechnicznych - Lewandowska, Patrycja; Jakoniuk-Diallo, Anna (Studia Edukacyjne, 2023)
The perception of a person with a disability is determined by qualities that are commonly desired in society. In this text, we have attempted to analyze to what extent the contemporary normalization paradigm, which assumes the necessity of treating every person with the dignity that belongs to them, while respecting their rights, translates into social perceptions of people with intellectual disabilities. For this we used a diagnostic survey, conducted among non-humanities (technical programs) students, i.e. young adults with theoretically less knowledge of psychology, sociology, or pedagogy, which could significantly affect what they think about people with intellectual disabilities. In the text, we also touched on social barriers, social tasks, and opportunities for people with intellectual disabilities.